Pelatihan Membaca Simbol Bunyi pada Kamus Bagi Guru Bahasa Inggris SMP dan SMA di Kabupaten Jayapura - Ferdinandus, Adelce Sisilia; Rahayu, Budi (Universitas Cenderawasih, 2023)
The teacher's knowledge and skills in using the dictionary as a learning reference are important. For example, in preparing teaching materials for students, teachers need to master the material to be taught. This includes knowing what the words in the text mean, how to say the words, and how to use them. By knowing the sound symbols in the dictionary and continuing to practice using them, teachers will be more prepared and confident in preparing material and presenting it to students. This is the background of this training. The training activities were carried out for one day with discussion and exercise methods. The activity was held at SMA Negeri 1 Sentani and was attended by 12 teachers from schools in Jayapura Regency. The survey results at the beginning of the training showed that most of the teachers did not know how to read sound symbols in a dictionary and had never heard the term sound symbol before. After this training the participants can sound sound symbols and are given some references to be able to continue practicing after the activity is over.